2018
DOI: 10.1016/j.arbres.2017.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Overall Survival Analysis and Characterization of an EGFR Mutated Non-Small Cell Lung Cancer (NSCLC) Population

Abstract: Background: Patients with activating somatic mutations in the Epidermal Growth Factor Receptor (EGFR) have better clinical outcomes when treated with Tyrosine Kinase Inhibitors (TKI) over chemotherapy. However, the impact of the use of TKIs on overall survival outside clinical trials is not well established. Objective: To characterize and analyze the overall survival of a Caucasian population with NSCLC and EGFR mutations. Methods: A retrospective cohort analysis of patients with NSCLC screened for EGFR mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 32 publications
3
3
0
Order By: Relevance
“…Indeed, previously published studies have also highlighted the NGS superiority over the traditional methods [25,26,27]. Although not an epidemiological study, mutation patterns and frequencies agree with previous data published on our population [28].…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, previously published studies have also highlighted the NGS superiority over the traditional methods [25,26,27]. Although not an epidemiological study, mutation patterns and frequencies agree with previous data published on our population [28].…”
Section: Discussionsupporting
confidence: 91%
“…Our data show an expected median OS of 12.0 months. This is similar to that reported in a retrospective cohort analysis of patients with NSCLC screened for EGFR mutations between October 2009 and July 2013, in which the median survival of the global population was 12.0 months, with a better OS in mutated than in nonmutated patients (20.0 vs. 11.0 months, respectively; P = 0.007) [27]. However, the populations of both studies are not comparable, since our population was preselected to have completed two lines of active treatment.…”
Section: Discussionsupporting
confidence: 88%
“…The median overall survival within the EGFR -mutated subgroup surpassed that of the wild-type EGFR cohort. Similar findings were reported in a distinct study encompassing a Caucasian population of 285 non-small-cell lung cancer patients, wherein patients with EGFR mutations demonstrated a markedly prolonged overall survival compared to their wild-type EGFR counterparts [ 37 ]. Furthermore, within an Asian patient cohort of 424 cases, Zheng et al reported that patients with EGFR mutations experienced a significantly longer survival duration to those with wild-type EGFR [ 38 ].…”
Section: Discussionsupporting
confidence: 85%